A RARE CASE OF DYSPNEA - Petre, Olvis; Irma, Tashi Bani; Jola, Hasani; Justi, Shestani; Silvana, Bala; Hasan, Hafizi (International Journal of Research -GRANTHAALAYAH, 2023)
Idiopathic dilatation of the pulmonary artery defines the presence of a benign enlargement of the pulmonary trunk with or without the involvement of the rest of the arterial tree in the absence of a detectable cardiac or arterial systemic disorder. An IDPA patient’s symptoms and physical examination are not significant in diagnosis confirmation. Imaging techniques such as contrast-enhanced computed tomography, right heart catheterization, and angiocardiogram constitute the foundation of IDPA diagnosis. But an extended observation period is also necessary to exclude other possible dilatation explanation. Our patient, a forty-six-year-old female, was admitted to the Pulmonology clinic of “ShefqetNdroqi” University Hospital with dyspnea, dry cough, vertigo, and fatigue for several months before admission. The patient’s contrast-enhanced Computed Tomography revealed a dilatation of the pulmonary trunk. The dilatation of the pulmonary trunk was confirmed with the Cardiac CT, and other abnormalities were excluded.